A Diagnostic Test on Grammatical Structures for English Teachers - Agnes Siwi Purwaning Tyas (Indonesian Journal of English Language Studies (IJELS), 2015)
Grammar is a significant part of English proficiency. English proficiency also covers communicative linguistic aspects that require the speakers to comprehend and use the linguistic aspects of language, as well as their functions and rules (Common European Framework of Reference for languages, 1971). Considering the importance of grammar accuracy in English proficiency, teachers need to master the language forms, the functions and the contexts of use before they can share their knowledge to their students. In order to measure teachers‘ proficiency on grammatical structures, this research is conducted to design a diagnostic test. A needs analysis questionnaire was distributed to 24 English teachers to identify the grammatical structures that they need to review and the urgency. The result of the questionnaire was used to determine the number of test items for each structure. The results of the diagnostic test were used to design a review program to help teachers review and improve their competence on grammatical structures based on their needs.